Enhanced expression of codon optimized Mycobacterium avium subsp. paratuberculosis antigens in Lactobacillus salivarius - Johnston, Christopher D.; Bannantine, John P.; Govender, Rodney; Endersen, Lorraine; Pletzer, Daniel; Weingart, Helge; Coffey, Aidan; O'Mahony, Jim; Sleator, Roy D. (Frontiers in Cellular and Infection Microbiology, 2014)
It is well documented that open reading frames containing high GC content show poor expression in A+T rich hosts. Specifically, G+C-rich codon usage is a limiting factor in heterologous expression of Mycobacterium avium subsp. paratuberculosis (MAP) proteins using Lactobacillus salivarius. However, re-engineering opening reading frames through synonymous substitutions can offset codon bias and greatly enhance MAP protein production in this host. In this report, we demonstrate that codon-usage manipulation of two MAP genes (MAP2121c and MAP3733c) can enhance the heterologous expression of two antigens (MMP and MptD respectively), analogous to the form to which they are produced natively by MAP bacilli. When heterologously over-expressed, antigenic determinants were preserved in synthetic MMP proteins as shown by monoclonal antibody mediated ELISA. Moreover, MMP is a membrane protein in MAP, which is also targeted to the cellular surface of recombinant L. salivarius at levels comparable to MAP. Additionally, codon optimised MptD displayed the tendency to associate with the cytoplasmic membrane boundary under confocal microscopy and the intracellularly accumulated protein selectively adhered with the MptD-specific bacteriophage fMptD. This work demonstrates there is potential for L. salivarius as a viable antigen delivery vehicle for MAP, which may provide an effective mucosal vaccine against Johne’s disease.